2010
DOI: 10.1044/1092-4388(2010/09-0093)
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Explanations for Preschoolers' Lowercase Alphabet Knowledge

Abstract: Findings suggest that transference from uppercase letter knowledge may be a primary mechanism for lowercase letter knowledge and that young children's knowledge of the lowercase alphabet letters is multiply determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 53 publications
7
37
1
Order By: Relevance
“…For example, in their experiences with environmental print and shared book reading, children are much more likely to encounter the uppercase letter T and lowercase letter e than they are to encounter letters such as Z and q . Some studies have found that children are more likely to know the names of more frequent letters (Pence Turnbull et al., ), but others have found that children show no difference in their knowledge of individual letters based on frequency (Evans, Bell, Shaw, Moretti, & Page, ; Treiman & Kessler, ; Treiman et al., ).…”
Section: Differences Across Lettersmentioning
confidence: 99%
“…For example, in their experiences with environmental print and shared book reading, children are much more likely to encounter the uppercase letter T and lowercase letter e than they are to encounter letters such as Z and q . Some studies have found that children are more likely to know the names of more frequent letters (Pence Turnbull et al., ), but others have found that children show no difference in their knowledge of individual letters based on frequency (Evans, Bell, Shaw, Moretti, & Page, ; Treiman & Kessler, ; Treiman et al., ).…”
Section: Differences Across Lettersmentioning
confidence: 99%
“…First steps towards literacy often involve teaching children about individual letters and the sounds the letters represent [3] [32] [57]. These first steps involve a) letter naming, b) phonics, and c) phonemic awareness approaches [8] [29] [58].…”
Section: Research On Letter and Letter-sound Teaching Strategiesmentioning
confidence: 99%
“…Some researchers have looked for frequency effects in children’s learning of letter names by examining the frequency with which letters occur in books, or specifically in books that are designed for children. Such effects are small and in some cases not statistically significant among 3- to 5-year-old learners of the Latin alphabet (Ecalle, 2004 for French; Evans et al, 2006; Treiman & Kessler 2004; Treiman et al, 2006, 2007; Turnbull, Bowles, Skibbe, Justice, & Wiggins, in press for English). However, the effects appear to increase with age (Bouchière, Ponce, & Foulin, 2010 for French), and a study of Israeli 5- and 6-year-olds found statistically significant frequency effects in letter naming (Treiman et al, 2007).…”
Section: Introductionmentioning
confidence: 92%
“…These models are increasingly used in psycholinguistic research with adults. In studies of children’s letter learning, they have been used so far only with English and only with the dependent variable of correct responses (Justice et al, 2006; Kim et al, 2010; Piasta & Wagner, 2010; Turnbull et al, in press). In the present study, we used multilevel models to analyze several types of responses in the letter-sound task, including both C and CV responses as defined earlier.…”
Section: Introductionmentioning
confidence: 99%